Prophylaxis of Upper Airway Infections in a Patient with Partial IgA Deficiency: Concurrent Use of Sublingual Immunotherapy with Inactivated Whole-Cell Bacterial Extract and Der p1 - Aarestrup, Paula F.; Aarestrup, Matheus F.; Aarestrup, Beatriz J. V.; Aarestrup, Fernando M. (Case Reports in Otolaryngology, 2020)
Selective IgA deficiency is the most common type of primary immunodeficiency, but there is not yet a specific effective treatment. The most prevalent clinical manifestations are infectious diseases of the respiratory system. We report herein the case of an 11-year-old female with selective IgA deficiency and recurring episodes of respiratory infections associated with rhinitis and asthma. We evaluated the efficacy of sublingual immunotherapy combined with inactivated whole-cell bacterial extract and Der p1-specific immunotherapy. After 18 months of clinical follow-up, we observed a significant reduction in the number of episodes of respiratory infections associated with control of atopic diseases. We also observed a 3-fold increase in serum IgA levels compared to treatment initiation. This case demonstrates the potential utility of the concurrent use of sublingual immunotherapy with inactivated whole-cell bacterial extract and Der p1 for successful control of allergy and infection in partial selective IgA deficiency.